First records of the genera Chagria and Davmata from China (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini), with descriptions of two new species - Cao, Yanghui; Huang, Min; Zhang, Yalin (Zootaxa, 2011)
Two oriental genera of Erythroneurini, Chagria Dworakowska and Davmata Dworakowska, are reported from China for the first time, each based on a new species: Chagria camptoprocessa and Davmata falcata spp. nov. Illustrations and keys to males for each genus are provided.